Long-lasting complete response to SHR-1701 plus famitinib in refractory advanced gallbladder cancer: A case report - Lixia Yi; Xiaoyan Zhu; Jing Xie; Zhiqiang Meng (Human Vaccines & Immunotherapeutics)
Biliary tract cancer (BTC) is an aggressive malignancy with few options for advanced-stage treatment. The combination of PD-1/PD-L1 inhibitors with famitinib, a receptor tyrosine kinase (RTK) inhibitor, has demonstrated improved clinical outcomes in several clinical trials. We herein reported a case of a gallbladder cancer (GBC) patient with liver metastases, previously resistant to traditional chemotherapy. Remarkably, the patient achieved a complete response (CR) with a long-lasting survival benefit exceeding 3 years. This was achieved using a novel regimen combining SHR-1701, an anti-PD-L1/TGF-βR fusion protein, and famitinib, even though the patient had proficient mismatch repair (pMMR) and tested negative for PD-L1. Adverse events were limited and manageable. This is the first report of such a treatment regimen being applied in a clinical setting, suggesting that the SHR-1701 and famitinib combination may be a promising immunotherapeutic approach for patients with refractory advanced GBC.